Effects of carrageenan on the stability and textual properties of shirmp balls - Nisperos, Jocelyn N.; De Leon, Sonia Y. (1992.)
The objective of this study was to assess the effects of carrageenan on the stability and textural properties of shrimp balls. It was divided into two phases. The first phase dealt with the determination of the best carrageenan to be incorporated into shrimp balls. Results of the sensory evaluation showed that the carrageenan--kappa, iota, and their blend at 0.5% level had no significant effect on the hardness, chewiness, juiciness, and general acceptability of the product. On the other hand, the objective tests showed that carrageenans were effective at improving the moisture content (MC) and water-holding ability (WHA) of the product. Data revealed that the kappa-iota carrageenan blend had the highest moisture content (71%) and also had the highest ability to hold moisture (55%) when subjected to mechanical stress i.e. centrifugal force. Kappa carrageenan increased the hardness of shrimp balls to almost equal to control when tested for tenderness using the Penetrometer. Iota carrageenan and the blend made the shrimp balls softer than the control. In phase II, the effects of increasing concentrations of kappa-iota blend were evaluated. Kappa-iota blend was the type chosen based on its highest water-holding ability and moisture content and samples with the blend also was the second most preferred by panelists and was not significantly different in ranking with the most preferred sample, the one with iota carrageenan. Results of the sensory evaluation showed that the hardness decreased, but the difference was not significant. Chewiness did not vary among samples. The juiciness of the shrimp balls increased with increasing concentrations of carrageenan, as perceived by panelists. The products were given hedonic ratings like slightly, for samples with 0.5% carrageenan blend and for all the other treatments, like moderately. Moisture content increased significantly from 62.9% to 68.4% for the carrageenan treatment of 0.5% and 1.5%, respectively. The water-holding ability (WHA) also increased from 48.3%, for samples containing 0.5% carrageenan, to 61.1%, for samples with 1.5% carrageenan. The tenderness of the product was not affected by gum concentration as shown by the results of the Penetrometer test.
Thesis (BSFT)--University of the Philippines Diliman.
Keywords: Chondrus crispus; Carrageenan